Leadership competencies within BIM-oriented project management; based on an analysis of project manager and BIM manager - Hu, Chunliang (My University, 2023)
Over the past 20 years, the construction industry has faced numerous challenges in terms of project performance and efficiency. Fragmentation, coordination complexities, ineffective communication, and inadequate planning have hindered effective collaboration among multidisciplinary actors. Collaboration failures, caused by inconsistent standardization, complex contracts, and multi-actor behavior, have led to project planning issues, delays, and cost overruns. To overcome these challenges, Building Information Modelling (BIM) has been identified as a technology that facilitates collaboration among multidisciplinary teams involved in BIM projects. However, success in BIM-based construction projects relies heavily on the efficiency, behaviors, and skills of leadership aspects throughout the project lifespan. Project leaders must possess a range of competencies, including both hard skills (software and modeling skills, data management, presentation skills) and soft skills (communication, negotiation, and decision-making skills). Leadership plays a critical role in comprehending the project life cycle and leveraging information across design, construction, and facility management stages. Individuals possess unique leadership characteristics that can either benefit or hinder the implementation of BIM. Therefore, understanding the valued leadership characteristics in BIM-oriented construction projects is essential. This paper aims to explore different leadership competencies of mainly project managers and BIM managers within BIM oriented projects and identify the suitable leadership competencies for BIM project management, focusing on improving project performance.
Keywords: leadership competency, BIM-oriented projects management, communication, construction 4.0, project managers, BIM managers